Effects of Acute Elevation in Blood Pressure and of Atropine on Heart Rate in Chagas' Disease: A Preliminary Report - AMORIM, D. S.; GODOY, R. A.; MANÇO, J. C.; TANAKA, A.; GALLO, L. (Circulation (New York, N.Y.), 1968)
Degeneration of the parasympathetic ganglia in the heart and in the smooth muscle (esophagus, colon, and bronchi) is known to occur in Chagas' disease. The reflex bradycardia associated with acute elevation in systemic arterial pressure and the blocking of this reflex effect with atropine are used in this investigation to study vagotonic influences on the heart in patients with Chagas' disease. Failure to increase heart rate following administration of atropine observed in cases of chronic Chagas' heart disease is believed to be a functional disorder related to degeneration of the neuronal supply to the sino-atrial region of the heart. To the authors' knowledge this report provides the first existing physiological investigation concerning the cardiovascular system in Chagas' disease.